Perioperative nutrition in bariatric surgery - Sutanto, Luciana Budiati (World Nutrition Journal, 2024)
Many patients think very simply about bariatric surgery, namely that after surgery the body soon becomes slim. In reality, carrying out bariatric surgery still follows the medical surgical procedure with all its complications, so the doctor must carry it out medically well and it would be ideal to follow standard guidelines.